2023
DOI: 10.1186/s13018-023-03648-1
|View full text |Cite|
|
Sign up to set email alerts
|

How high is the quality of the videos about children's elbow fractures on Youtube?

Abstract: Objective Pediatric elbow fractures are children's most common fractures. People use the internet to get information about their illnesses and also to search for treatment options. Videos uploaded to Youtube do not go through the review process. The aim of our study is to determine the quality of videos related to child elbow fractures on Youtube. Material method The study was carried out with the data obtained from the video-sharing site www.youtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
7
1
Order By: Relevance
“…This paper from the international Perthes' study group, based in the USA, looked at the question of whether reducing weightbearing results in increased BMI. 7 To our knowledge, this is the first paper to address this question for this pathology, and the request for restricted weightbearing is a common complaint of patients in clinic. Using their prospectively collected international database, 130 patients with early-stage Perthes' aged five to 12 years were included in the study.…”
Section: Weightbearing Restrictions and Weight Gain In Children With ...mentioning
confidence: 98%
See 1 more Smart Citation
“…This paper from the international Perthes' study group, based in the USA, looked at the question of whether reducing weightbearing results in increased BMI. 7 To our knowledge, this is the first paper to address this question for this pathology, and the request for restricted weightbearing is a common complaint of patients in clinic. Using their prospectively collected international database, 130 patients with early-stage Perthes' aged five to 12 years were included in the study.…”
Section: Weightbearing Restrictions and Weight Gain In Children With ...mentioning
confidence: 98%
“…In this study from Adana (Turkey) , a team has searched YouTube for videos that aim to provide information on paediatric elbow fractures and have made an assessment of their quality. 7 The videos found on a wide-ranging search on a single day were characterized by the organization or individual that produced them, and the quality assessed using the Global Quality Scale (GQS) by two researchers. Overall, 50 videos were included in the analysis.…”
Section: Youtube and Paediatric Elbow Injuriesmentioning
confidence: 99%
“…Internet resources play a key role in the spread of health information, so patient involvement is a leading marker for decision-making outcomes [ 1 , 2 ]. The active role played by patients is mediated by the quality and readability of Internet resources, and disentangling this network is not simple [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…This collaborative knowledge can improve health professionals' approach to mutual interaction for a shared decision-making process [ 4 ]. In a patient-centered delivery model, accessing the right health information online can help patients become active participants in the information process [ 2 ]. For this reason, improving health literacy among patients, by translating academic knowledge and information into a more practical pattern, is vital to support this conscious interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the author reported that the affiliations of the authors are incorrect. The correct version of affiliations is provided in this correction.…”
mentioning
confidence: 99%